LncRNA DLX6-AS1 promoted cancer cell proliferation and invasion by attenuating the endogenous function of miR-181b in pancreatic cancer - An, Yong; Chen, Xue-min; Yang, Yong; Mo, Feng; Jiang, Yong; Sun, Dong-lin; Cai, Hui-hua (Cancer cell international, 2018)
Pancreatic cancer, one of the most aggressive malignancies, ranks the fourth cause of cancer-related death worldwide. Aberrantly expressed long non-coding RNAs (lncRNAs) functioned as oncogenes or tumor suppressors in pancreatic cancer. This study aimed to determine the expression of lncRNA DLX6 antisense RNA 1 (DLX6-AS1) in pancreatic cancer tissues and to explore the DLX6-AS1-related pathway in pancreatic cancer. The gene expression levels were determined by quantitative real-time PCR, and protein expression levels were determined by western blot assay. CCK-8 assay, colony formation assay and Transwell migration and invasion assays were used to examine cell proliferation, migration and invasion. Luciferase reporter assay was used to confirm the binding between DLX6-AS1and its potential targets. In vivo study used the mouse xenograft model to test the anti-tumor effect of DLX6-AS1 knockdown. The high expression of DLX6-AS1 was observed in pancreatic cancer tissues, and high expression of DLX6-AS1 was positively correlated with larger tumor size, advanced TNM stage and lymph node metastasis. Knockdown of DLX6-AS1 dramatically impaired cancer cell proliferation, migration and invasion. MiR-181b was the downstream target of DLX6-AS1. Knockdown of miR-181b reversed the suppression of cell viability, migration and invasion abilities caused by DLX6-AS1 knockdown. MiR-181b was found to target Zinc finger E-box-binding homeobox 2 and to modulate epithelial-mesenchymal transition. Furthermore, DLX6-AS1 knockdown inhibited tumor growth and tumor metastasis in vivo. Collectively, our data suggested that DLX6-AS1 promotes cancer cell proliferation and invasion by attenuating the endogenous function of miR-181b in pancreatic cancer.